Analisis Kepuasan Pelanggan Pengguna Jasa Transportasi Ojek Online: Studi Pada Pengguna Grab Bike - Chalimatuz Sa'diyah; Dian Aulia; Sri Nastiti Andharini (Fakultas Ekonomi Universitas Islam 45, 2021)
This study aims to determine the influence of service quality, price, and brand image toward customer satisfaction on GrabBike online transportation services in Malang City, either partially or simultaneously. The population in this study comes from the customers who use the GrabBike online transportation in Malang City which consists of 100 respondents. The sampling technique that used in this study is purposive sampling with the respondent's criteria, namely the Malang citizens who used GrabBike more than three times in less than six months and have Grab application on their own smartphone. The results of this study indicates that service quality, price, and brand image has a positive and significant impact toward customer satisfaction on using GrabBike online transportation services in Malang City, either partially or simultaneously. Based on the results of this study, it can be concluded that service quality, price, and brand image has a positive and significant impact toward customer satisfaction on using GrabBike online transportation services in Malang City.